Collaborative storytelling in distance education: a preliminary research with pre-school children - Gasparini, Silvia (Form@re - Open Journal per la formazione in rete, 2021)
Distance education was adopted in schools in many countries around the world as a result of the COVID-19 pandemic during 2020. Especially for pre-school children, distance education presents many critical issues, including children’s sense of isolation and poverty of interactions with peers. In order to overcome these limitations, it is necessary to think about how to redesign didactic activities normally carried out in class without penalizing the relational aspect. This research deals with collaborative storytelling, considered an important tool for the development of emotional, cognitive and social processes as well as a means for media literacy education in children aged 3-6. Specifically, the experiment aims to compare the use of three ways of collaboratively narrating fictional stories in asynchronous mode. Results show that when the children alternate in the roles of author/critic and coordinator/author, stories are more coherent in terms of relationship and continuality of story elements and children’s perception of positive interdependence is greater than in the co-author condition. Lo storytelling collaborativo nell’educazione a distanza: una ricerca preliminare con bambini della scuola dell’infanzia L’educazione a distanza a seguito della pandemia da Covid-19 del 2020 è stata adottata nelle scuole di molti stati. Specialmente per i bambini di età prescolare, questa modalità didattica presenta numerose criticità, fra le quali vengono segnalati il senso di isolamento dei bambini e la povertà delle interazioni fra pari. Al fine di ovviare a questi limiti è necessario pensare a come realizzare a distanza le attività didattiche normalmente svolte in presenza senza penalizzare l’aspetto relazionale. Nella presente ricerca viene affrontato il tema dello storytelling collaborativo, ritenuto un importante strumento di sviluppo per i bambini nella fascia di età 3-6 anni. Nello specifico, l’esperimento si propone di confrontare l’utilizzo di tre modalità alternative di costruire storie di fantasia in forma collaborativa a distanza in modalità asincrona. I risultati dimostrano che quando i bambini si alternano nei ruoli di autore/critico e di coordinatore/autore, le storie risultano più coerenti in termini di relazione e continuità fra gli elementi della storia e la percezione di interdipendenza positiva dei bambini cresce rispetto alla condizione in cui i bambini assumono il ruolo di co-autori della storia.